Synthesis of spirostanol saponins via gold(I)‐catalyzed glycosylation in the presence of Ga(OTf)3, In(OTf)3, or HOTf1. Issue 8 (16th July 2019) - Ehianeta, Teddy Stephen; Shen, Dacheng; Xu, Peng; Yu, Biao
Summary of main observation and conclusion: An effective approach relying on a Lewis acid‐ or Brønsted acid‐assisted gold(I)‐catalyzed glycosylation has been reported in the synthesis of a panel of the representative natural spirostanol saponins, namely polyphyllin D (1 ), polyphyllin V (2 ), dioscin (3 ), formosanin C (4 ), and a derivative of polyphyllin D bearing a terminal azide group (5 ). This approach highlights the engagement of low loadings of Ph3 AuPOTf (≤ 0.5 mol%) in the presence of Ga(OTf)3, In(OTf)3, or HOTf (~10mol%) as a co‐catalyst, at practical reaction rates as an alternative to the conventional ~10 mol% loadings of the gold(I) catalyst in the glycosylation. Polyphyllin D (1 ) was obtained in 41% overall yield over six steps compared to the maximum 30% yield in previous syntheses where conventional donors and promoters were used. By exploiting a regioselective rhamnosylation, a "one‐pot" approach was adopted to assemble1 and5, thus further strengthening the efficiency of the gold(I)‐catalyzed glycosylation. Abstract : A panel of bioactive spirostanol saponins are synthesized via glycosylations catalyzed by ≤0.5 mol% gold(I) complex in the presence of Ga(OTf)3, In(OTf)3, or HOTf.